Perilaku Pengguna Toilet Umum - Mafra, Ramadisu; Riduan, Riduan; Zahra, Sabrina Alifa; Bahtiar, M Apis; Romdani, Ridho (Arsir, 2020)
Going to public toilets is not an option but a necessity, while the design and amenities of public toilets at the Mall offered are more oriented to Western standards, with perspectives around luxury, meditation, health, and cleanliness, without the study of how the user community perceives toilets according to their culture. The phenomena of culture shock due to failure to adapt often results in misconduct. This study aims to find the phenomenon of misconduct in the use of public toilet facilities and their causes. Involving 318 random purpose informant samples of public toilet users in the six Palembang Mall, collecting data using questionnaires and interviews, the data were processed with a central tendency analysis for three variables. The results found maladjusment at seating toilet by 24.53% of users, 66.10% in the use of Jetspray, leaving the toilet without washing hands in washtafel 75.93% and not using the hand drayer 72.59%, caused by 45,15% of users are unfamiliar, avoid impure 31.63%, cleanliness 34.26%, and afraid of being dirty 23.22%.